Weed Control Strategies for Restoration of the Atlantic Forest in the State of Rio de Janeiro - Brazil - Lisboa, Alysson Canabrava; Silva, Charles Oliveira da; Santos, Alinne Rocha; Santana, João Elves da Silva; Antunes, Luiz Fernando de Sousa; Leles, Paulo Sérgio dos Santos (Fronteira: Journal of Social, Technological and Environmental Science, 2023)
The objective was to evaluate the best weed control strategy, for the formation of forest stands in Atlantic Forest, Brazil, aiming at restoration in an area dominated by Urochloa decumbes, evaluating the biological indicators and costs. It also sought to verify the magnitude of response of mechanical control compared to treatment without intervention, for similar sites where the experiment was installed and conducted. The treatments were: T1 - mechanical (mowing and crowning); T2 - chemical (application of glyphosate syrup); T3 - mechanical cultural (weeding, seeding and cultivation of Cajanus cajan and Canavalia ensiformes); T4 - chemical cultural (application of glyphosate, seeding and cultivation of legumes); T5 - absolute control (no intervention after planting). Activities and evaluations were carried out up to 30 months after planting the seedlings of the five species used. It was observed that in all treatments the survival of the plants reached values higher than 80%, at 6 and 18 months after planting. It was found that, on average, the tree plants in T2, T3, and T4 showed significantly higher growth than those in T1 and T5, which did not differ. The control with glyphosate is indicated for areas with predominance of Urochloa sp. Strategy control with glyphosate and cultivation of herbaceous legumes has potential use and needs adjustments to reduce costs. Also, that the control with mowing and crowning is not indicated due to the high cost and not favoring the growth of the planted trees, because it did not show significant differences in relation to the controls.